Challenging Cough Cases: A Protocolized Approach. (2nd September 2014) - Altman, Kenneth W.; Krouse, John H.; Luong, Amber U.; Lane, Andrew P.; Carroll, Thomas L.; Rosen, Clark A.
Abstract : Program Description: Chronic cough is an increasingly important public health concern, accounts for a large number of ambulatory care visits, and often involves a protracted clinical course. Otolaryngologists play a critical role in the care of these patients because of our interdisciplinary approach to the aerodigestive tract and our mastery of many procedures used to evaluate and treat related conditions. This miniseminar will present challenging cases with panel discussion and audience participation to emphasize evidence‐based practice and the "state‐of‐the‐art" for patients with chronic cough. Controversial areas will include prioritization, the use of evidence‐based protocols, and the importance of early diagnosis in value‐based health care. Educational Objectives: (1) Describe evidence‐based treatment guidelines in the evaluation and treatment of chronic cough. (2) Use the spectrum of common and uncommon causes of chronic cough with an appreciation of the underlying physiology. (3) Evaluate these complex patients, perform objective testing when indicated, and prescribe appropriate pharmacotherapy for patients with chronic cough.